Rapidly Separable Micropillar Integrated Dissolving Microneedles - Jung, Chung-ryong (Pharmaceutics, 2020)
Dissolving microneedle (DMN) patches were developed as efficient and patient-friendly transdermal delivery systems for biopharmaceuticals. However, recent studies have confirmed that the efficiency of DMNs to deliver biopharmaceuticals is highly reduced because of incomplete insertion caused by the stiffness and elastic properties of the skin. Therefore, micropillar integrated DMNs were developed to overcome the insertion limitations of DMN patches. Although micropillars were designed as integrated applicators to implant DMNs across the skin, they can also become inserted into the skin, leading to skin injury and inflammation. Herein, we have developed a separable micropillar integrated DMN (SPDMN) capable of inserting DMNs across the skin with high efficiency while minimizing skin injury risk through the introduction of a safety ring feature. Unlike previously developed systems, the SPDMN does not require continuous skin attachment and can be detached immediately post-application, leaving DMNs implanted inside the skin. Altogether, the findings of this study lead to the development of a quick, safe, and efficient DMN-based drug delivery platform.